Impact of surgical training on patient safety in low-middle-income countries - Sana Zeeshan; Amber Sultan; Hina Inam; Nadeem Siddiqui (Journal of the Pakistan Medical Association, 2026)
Surgical training is a critical determinant of patient safety, especially in low- and middle-income countries. The current narrative review was planned to discuss the role of surgical training in low- and middle-income countries, specifically the quality of training, availability of resources and gaps in systems, to show how inadequacies in structures, supervision and compliance with standard operating procedures make patients vulnerable to unsafe care. Alternative strategies, including simulation training, public-private partnerships and task-sharing, were analysed for their effectiveness in addressing specific problems. Country-specific efforts from Pakistan, Kenya and Nigeria reported certain achievements as well as challenges in the way of meeting international practices. The role of global instruments, such as World Health Organisation Surgical Safety Checklist and Accreditation Council for Graduate Medical Education core competencies on surgical practice’s safety, was also assessed to bolster surgical training in low- and middleincome countries as a means of improving health outcomes, securing fairness in healthcare, and achieving designated aims of international health strategies. Keywords: Surgical training, Patient safety, Simulation training, WHO safety checklist, Low- and middle-income countries, Global health..